Effects of Dietary Prebiotics (SafMannan) and Local Iraqi Prebiotic on Some Blood Biochemical Parameters of Broiler Chickens - Ali, Nihad Abdul-Lateef; Jameel, Yasser; Abbas, Rabia J. (Pakistan Journal of Nutrition, 2018)
Background and Objectives: This study was undertaken to investigate serum biochemical constituents of broiler chickens after incorporating a prebiotic (SafMannan, from Plileo Co.) and a local Iraqi prebiotic as feed additives. Methodology: A total of 195 straight run day-old broiler chicks (Ross 308) were randomly assigned to five experimental groups with 39 birds/group. Each group was subdivided into 3 replicates (13 birds/per replicate). The first group was fed a basal diet as a control group. The second and third groups were fed the basal diet supplemented with the SafMannan prebiotics at the level of 250 g t–1 (Saf 250) and 500 g t–1 (Saf 500), respectively. Meanwhile, the fourth and fifth groups were fed the basal diet supplemented with the local Iraqi prebiotics at the level of 250 g t–1 (IQP 250) and 500 g t–1 (IQP 500), respectively. Results: The results revealed a significant (p≤0.05) effect of SafMannan (Saf) and local Iraqi prebiotics (IQP) on the decrease in serum glucose, cholesterol, triglyceride concentration and aspartate transaminase (AST) enzyme activity in all dietary groups compared to the control. The group of Saf 250 and IQP 250 showed higher (p≤0.05) total protein and high-density lipoprotein cholesterol (HDL-c) levels. Conclusion: Supplementation of broiler chickens’ diets with 250 and 500 g t–1 of SafMannan prebiotic and Iraqi prebiotics led to improve serum lipid profiles and serum protein parameters. SafMannan prebiotics performed best by influencing serum blood indices compared to local Iraqi prebiotics.